Pengaruh Penerapan Etika Profesi Terhadap Kepercayaan Masyarakat Pada Akuntan Publik - Arasyid, Rafi Ar.; Gunawan, Allysa Putri; Kayla, Aurelia Nadda; Puspita, Salsabillah Dwi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the influence of professional ethics implementation on public trust in public accountants in Indonesia, focusing on principles from the Indonesian Institute of Accountants (IAI) Code of Ethics such as integrity, objectivity, professional competence, and confidentiality. A qualitative approach was employed through an in-depth literature study, involving the collection and synthesis of secondary data from national journals, international professional standards like IFAC, and documented cases of public accountant ethics violations in academic literature from 2020-2025. Thematic content analysis techniques were applied to identify patterns in the relationship between professional ethics implementation and dimensions of public trust, including perceptions of financial reporting transparency, audit credibility, and the impact of ethics violations on professional reputation.This research contributes theoretically by integrating stakeholder theory and agency theory in the context of Indonesian accounting ethics, while providing practical recommendations for IAI and KAP to enhance ethics training and oversight mechanisms. Limitations of the literature study lie in reliance on secondary data, suggesting future research with in-depth interviews among stakeholders.